Reversible capping/uncapping of phosphorous-centered Keggin-type polyoxoniobate clusters. Issue 8 (4th November 2014) - Son, Jung-Ho; Casey, William H.
Abstract : Caps in α-Keggin-type polyoxometalates [PM2 Nb12 O40 ] 9− (M: NbO or VO) can be removed in basic condition to produce uncapped [PNb12 O40 ] 15− . Transmetalation or capping occurs from the reaction of [PNb14 O42 ] 9− or [PNb12 O40 ] 15− with either Sb2 O3 or V2 O5 to form [PSb2 Nb12 O40 ] 9− or [PV2 Nb12 O42 ] 9−, respectively. Abstract : Caps in α-Keggin-type polyoxometalates [PM2 Nb12 O40 ] 9− (M: NbO or VO) can be removed in basic condition to produce uncapped [PNb12 O40 ] 15− . Transmetalation or capping occurs from the reaction of [PNb14 O42 ] 9− or [PNb12 O40 ] 15− with either Sb2 O3 or V2 O5 to form [PSb2 Nb12 O40 ] 9− or [PV2 Nb12 O42 ] 9−, respectively.